Analysis of The Influence of Innovation Ambidexterity on The Quality of Public Services in Government Agencies - Susanto, Ahmad; Rochima, Emma; Kusumawati, Riny (Universitas Djuanda, 2025)
The low number of innovations produced by government agencies requires the presence of ambidextrous innovation to create effective and efficient innovations in public services. This study aims to analyze the direct influence of human resources, leadership, organizational structure, and organizational culture on ambidextrous innovation to further affect the quality of public services in government agencies, and examine the indirect influence of these variables on the quality of public services through ambidextrous innovation as a mediating variable. 113 public service agencies were selected as samples using purposive sampling techniques. Data were analyzed using path analysis to measure research variables' direct and indirect effects. The results showed that Organizational Structure is the only variable directly affecting Ambidextrous Innovation (p value = 0.007), while other variables do not. Ambidextrous innovation has a significant influence on the quality of public services (p-value = 0.001). In addition, only Organizational Structure significantly influences Public Service Quality through Ambidextrous Innovation as an intervening variable. This suggests that to improve the quality of public services, greater attention must be paid to developing organizational structures and processes that support innovation.